Distribution of some heavy metals in the sediments of Tigris river from sewage of Thermal Electrical Station at Baiji City in Salah-aldin Governorate-Iraq - Hiba Abd albast Hashim Alshaeghli; Riadh Abas Abdul Jabar; Hussain Hassan Kharnoob (Tikrit Journal of Pure Science, 2020)
This study was conducted to determine four  heavy metals including copper, zinc, lead and cadmium in the sediments of the Tigris river for a distance of 3,500 km for the time period autumn2012 – summer 2013.This is the first time that such a study carried out by the river sediments so studies on the Tigris river about sequential extraction to compare them with the results of the research not available, total concentrations recorded of  Cu )11.23-12.1)µg/g, Zn (39.6-41.03) µg/g, Pb (115.82-117.34) µg/g,Cd (4.1-4.34) µg/g dry weight, the distribution in the sediment layers, exchangeable metal ion recorded of Cu (0.42-0.44) µg/g, Zn (0.32-0.33) µg/g, Pb (0.22-0.25) µg/g, Cd (0.15-0.17) µg/g dry weight, and layer of carbonate bound of Cu( 1.6-1.63) µg/g ,Zn (4.47-6.71) µg/g, Pb (0.2-0.22) µg/g , Cd (1.44-2.17) µg/g dry weight, and the metal layer of Cu (1.26-1.41) µg/g, Zn  (15.84-17.07) µg/g, Pb  (46.38-49.46) µg/g, Cd  (1.9-2.17) µg/g dry weight, concentration of organic layer Cu (7.85-8.67) µg/g, Zn (17.63-17.96) µg/g, Pb (68.57-67.48) µg/g, Cd (0.58-0.86) µg/g dry weight. The arrangement of total concentration Pb>Zn>Cu>Cd (4,42-12,09-41,69-116,88) µg/g dry weight. Distribution of Cu organic layer> carbonate bound> metal layer> exchangeable metal ion (8,41-1,78-1.52-0.35) µg/g dry weight, Zn metal layer> organic layer> carbonate bound> exchangeable metal ion (18.99-17,58-5.52-0.29) µg/g dry weight, Pb organic layer>metal layer> exchangeable metal ion> carbonate bound (66.42-49.81-0.22-0.2) µg/g dry weight, Cd metal layer> carbonate bound> organic layer> exchangeable metal ion (2.02-1.87-0.91-0.18) µg/g dry weight .The high concentration recorded in four station, these results indicated that the possibility of using sequential extraction for the detection of the distribution of metals and determine the impact of diversity through release them to the aquatic environment, all concentration mentioned are rate they aren’t single value.